Succession Planning Promoting Organizational Sustainability (Springer International Publishing, 2018)
This book examines current research related to succession planning strategies and tactics. The authors compare and contrast the rationale and processes needed for effective and efficient succession planning. This is a comprehensive endeavor exploring succession planning across today's key disciplines: business, education, and healthcare. Succession planning is examined from the commercial, government, and non-profit lens. The book features active research, broad literature reviews, and examines conceptual frameworks. From this valuable contribution to succession planning research, readers will receive a thorough assessment of the theoretical foundations of succession planning and ethical considerations for sustainable leadership.